A new cross‐borehole hydraulic caving technique in the coal seam with a soft layer for preventing coal and gas outbursts during coal roadway excavation. Issue 4 (16th January 2020) - Qin, Binbin; Wei, Guoying; Lou, Zhen; Wang, Zehua; He, Fulian; He, Wenrui; Zhu, Hengzhong
Abstract: Predrainage of gas by cross‐boreholes is an important method to prevent coal and gas outbursts in the process of a coal roadway excavation. Limitations of technologies and poor effects of preventing coal and gas outbursts occur in the coal seam with a soft layer. In this study, a new hydraulic caving technology for cross‐boreholes has been proposed to solve this problem. A CT equipment was used to observe the development of coal fissures around cross‐boreholes in the coal seam with a soft layer. The plastic zone range and permeability distribution of ordinary hydraulic slotting technologies and the new hydraulic caving technology also were compared by numerical simulation. The field test of hydraulic caving was taken in the Xuehu Mine (China). The results show that the fracture development degree of soft coal is greater than that of hard coal at the same distance from cross‐boreholes. The fracture development degree in the plastic zone is greater than that in the elastic zone. The hydraulic caving technique can achieve the same effect as the ordinary hydraulic slotting with less workload. The mass of coal discharged from a cross‐borehole was 1.15 t/m and the average methane concentration of single drainage borehole increased by 1.09‐4.1 times, and the average methane extraction amount of single drainage borehole increased by 6.06 times. Elimination of coal and gas outburst had been completed after 110 days of extraction in the area of hydraulic caving, and Q and S values are lower than the critical value during roadway excavation. It is conclusion that hydraulic caving technique can effectively improve the permeability and rapidly eliminate coal and gas outburst in the coal seam with a soft layer. Abstract : A new hydraulic caving technique in the coal seam with a soft layer was proposed. Elimination of coal and gas outburst had been completed after 110 days of extraction in the area of hydraulic caving. This novel technology can effectively improve the permeability and rapidly eliminate coal and gas outburst in the coal seam with a soft layer.